What Happened to Novice EFL Teachers Professional Learning in Pesantren Based Billingual Program? Evidence from an Islamic Boarding School in East Lombok Indonesia - Marham Jupri Hadi; Mohammad Rudiyanto; Siti Wahyu Puji Anggraini; Lume L (IJEE (Indonesian Journal of English Education), 2018)
ABSTRACTThis study investigated the practice of professional learning as experienced by novice English Foreign Language (EFL) Teachers especially those teaching at Islamic Boarding Schools or Pesantren which ran English and Arabic language program. Case study was employed by involving English Teachers and a School headmaster. This study revealed EFL teachers found it challenging to manage classroom. This is partly caused by the class size and their limited experiences and authority to manage class. They also suffered from intimidating lesson plans design. Moreover, they found it daunting to encourage students to learning English, resulting in teachers' stress. Further, barriers of novice EFL teachers' professional learning were associasted with their attitude toward continous learning needs and limited programs to improve teachers' competency.  It also revealed that this pesantren and the school where this study was carried out have yet to set TPD programs for its teachers. In fact, novice EFL teachers were unlikely to get necessary supports from school and senior teachers despite the presence of informal supervision from senior teachers.  ABSTRAKPenelitian ini mengkaji praktik pembelajaran profesional guru Bahasa Inggris pemula, khususnya yang mengajar di Pesantren yang menerapkan program bahasa Inggris dan Arab. Penelitian dengan desain studi kasus ini melibatkan Guru Bahasa Inggris dan kepala sekolah. Hasil penelitian ini menunjukkan bahwa guru-guru bahasa Inggris tersebut menghadapi tantangan untuk mengelola kelas. Hal ini disebabkan oleh besarnya jumlah siswa di dalam satu kelas serta minimnya pengalaman dan wewenang mereka mengelola kelas. Mereka juga merasa terbebani oleh penyusunan rencana pelaksanaan pembelajaran. Mereka juga merasa kesulitan untuk memotivasi siswa belajar bahasa Inggris. Semua hal tersebut membuat guru-guru bahasa Inggris tersebut merasa tertekan. Hasil penelitian ini juga menunjukkan bahwa faktor yang menghambat pembelajaran guru bahasa Inggris pemula tersebut adalah sikap guru terhadap kebutuhan belajar secara berkesinambungan dan terbatasnya program peningkatan kompetensi guru. Pesantren dan sekolah tempat penelitian ini dilakukan ternyata menetapkan program pengembangan profesi untuk guru-gurunya. Selain itu, para guru bahasa Inggris pemula tersebut tidak juga mendapatkan dukungan yang diperlukan dari sekolah dan guru senior meskipun telah ada supervisi informal dari guru senior.     How to Cite: Hadi, M. J., Rudiyanto, M., Anggraini, S. W. P., Lume. (2018). What Happened to Novice EFL Teachers Professional Learning in Pesantren Based Billingual Program? Evidence from an Islamic Boarding School in East Lombok Indonesia. IJEE (Indonesian Journal of English Education), 5(2), 165-175. doi:10.15408/ijee.v5i2.10922